Characterization, antioxidant and antitumor activities of phenolic compounds from Amomum villosum Lour. - Zhang, Ming; Shuai, Xi-xiang; Wei, Zhi; Dai, Tao-tao; Wei, Chang-bin; Li, Ya; He, Jun-jun; Du, Li-qing (Frontiers in Nutrition, 2024)
Amomum villosum Lour. (A. villosum), known as Sharen in China, is widely used for culinary and medicinal purposes due to containing a diverse set of bioactive compounds. In this study, the optimum ethanol extraction process was optimized and the composition and biological activities (antioxidant and antitumor) of five different fractions (dichloromethane, petroleum ether, ethyl acetate, n-butanol and H2O) extracted from the ethanol extract of A. villosum were investigated. The results showed that the optimal extraction conditions were extraction temperature 80°C, extraction time 120 min, ethanol concentration 40% and solid–liquid ratio 1:25 g/mL. Moreover, 35 bioactive compounds were successfully identified by UPLC-ESI-QTOF-MS/MS from five factions for the first time, including 12 phenolic acids and derivatives, 2 organic acids, 12 flavonoids and derivatives, 2 oxylipins and 7 proanthocyanidins. Among them, ethyl acetate fraction (Fr-EtOAc) exhibited the highest content of total phenolic (374.01 mg GAE/g DW) and flavonoid (93.11 mg RE/g DW), where vanillic acid, catechin, epicatechin and protocatechuic acid were the predominant phenolic compounds that accounting for 81.65% of the quantified bioactive compounds. In addition, Fr-EtOAc demonstrated excellent total antioxidant activity (IC50 of DPPH and ABTS assays were 0.23, 0.08 mg/mL, respectively, and FRAP assay was 322.91 mg VCE/100 g DW) and antitumor activity (1,000 μg/mL, 79.04% inhibition rate). The results could provide guidance for the industrial production and application of A. villosum.